Kapag palay ang lumapit sa manok a study on men's perception of women making the first move in courtship and of a steady relationship - de los Reyes, Christine B. (1998)
Sixty Filipino men categorized as students and professionals were made to answer ann 11-item questionnaire regarding their perception of courtship and steady relationships. The results of the survey showed that 83% (50 subjects) agree that men should make the first move in courtship and 17% (10 subjects) feel that women should also be given the chance to woo the men. On the other hand, 50% of the respondents feel that a couple should share the privilege to make decisions, to pay the bills and to run the relationship. The results of which were tested under the .01 alpha level of confidence (6.64 value) and the computed value (.48) of the chi-square on the "men-women" response showed that the rate of responses between the students and professionals did not differ significantly. Similarly, the .69 value of the "yes-no" response showed homogeneity of samples with respect to their attitude about courtship and a steady relationship. Based on the results, men whether students or professionals, are most likely to agree to go steady with a woman who courts him as long as he likes that woman.